Effects of chemical slurries on fixed abrasive chemical-mechanical polishing of optical silicon substrates - Tian, Yebing (2016)
Chemical mechanical polishing (CMP) with fixed abrasive pad is an alternative machining method to loose abrasive lapping and partial polishing with traditional pad in the fabrication of optical silicon substrates. However, the effects of chemical slurry on the fixed abrasive polishing performance are not fully understood. In this work, a serial of CMP experiments with a fixed abrasive pad were carried out for optical silicon substrates using seven different chemical slurries i.e. de-ionized water, alkaline lubricant, colloidal silica, hydrogen peroxide (H2O2) and potassium hydroxide (KOH). The polishing performances of these slurries were evaluated and compared in terms of material removal rate (MRR), surface roughness and flatness of the polished silicon substrates. The polishing characteristics were also discussed to reveal material removal mechanism and silicon surface generation under different chemical environments.